Thermo-mechano-oxidative behavior at the ply's scale: The effect of oxidation on transverse cracking in carbon–epoxy composites. (15th December 2015) - Daghia, F.; Zhang, F.; Cluzel, C.; Ladevèze, P.
Abstract: The use of polymer matrix composites at relatively high temperatures (150–300°C) requires accounting for the oxidation of the polymer and its coupling with mechanical degradation. A vast body of literature investigates these phenomena at very small scales, from the chemistry of the polymer to the mechanical behavior at the fiber's scale. The aim of this work is to apprehend the effect of oxidation on the transverse composite properties directly at the ply's scale, and in particular to examine its effect on the evolution of transverse cracking during aging and mechanical loading. Experimental results demonstrated the appearance of a new cracking scenario with respect to unaged composites, and a model based on finite fracture mechanics enabled us to explore the competition between the two different mechanisms. This work is a first step towards a damage mesomodel which incorporates the effects of oxidation aging.